Analysis of Signature of Stainless Steel in Uzbekistan and Abroad - Kakharovich, Kasimov Umidjon; Karabaevna, Atakhanova Sayyora (International Journal on Human-Computing Studies, 2022)
This article analyses the branding of stainless steels in Uzbekistan and abroad, the types of steels according to their use, chemical composition, type of application, hot and cold resistant stainless steel coils.